2020
DOI: 10.2174/1381612826666191227154009
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Functions of the lncRNA TUG1

Abstract: Background: Long non-coding RNAs (lncRNAs) with little or no coding capacity are associated with a plethora of cellular functions, participating in various biological processes. Cumulative study of lncRNA provides explanations to the physiological and pathological processes and new perspectives to the diagnosis, prevention, and treatment of some clinical diseases. Long non-coding RNA taurine-upregulated gene 1(TUG1) is one of the first identified lncRNAs associated with human disease, which actively involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 130 publications
0
37
0
Order By: Relevance
“…Taurine-upregulated gene 1 (TUG1) is transcribed from a gene localized on chromosome 22 (22q12.2) and it is able to regulate gene expression through different mechanisms, since it interacts with Polycomb repressor complex and functions in the epigenetic regulation of transcription, but can also function in the cytosol sponging microRNAs [ 37 ]. Interestingly, this latter mechanism has been reported for microRNAs implicated in IL-1β, IL-6, IL-10 and TNFα signaling [ 21 , 22 ], and thus in processes involved in CD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine-upregulated gene 1 (TUG1) is transcribed from a gene localized on chromosome 22 (22q12.2) and it is able to regulate gene expression through different mechanisms, since it interacts with Polycomb repressor complex and functions in the epigenetic regulation of transcription, but can also function in the cytosol sponging microRNAs [ 37 ]. Interestingly, this latter mechanism has been reported for microRNAs implicated in IL-1β, IL-6, IL-10 and TNFα signaling [ 21 , 22 ], and thus in processes involved in CD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased NEAT1 expression could also represent a defense mechanism triggered by gluten exposure and IL-15 production. In fact, the modulation of the expression of NEAT1 or TUG1 has been reported by various groups as part of a protective response to different stimuli [ 19 , 37 ]. NEAT1 increases after the induction of oxidative stress in HUVEC cells, and this process in mediated by P53 activation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown that lncRNAs can play opposing roles and behave like oncogenes or tumor-suppressor genes during tumorigenesis, there is still no consensus about the biologic implications of these non-coding transcripts in the clinical setting (3). Prior studies have demonstrated the significant roles that lncRNAs play in fundamental cellular functions, such as pre-transcription, post-transcription, cell proliferation, invasion, differentiation, apoptosis, and migration (4). Increasing evidence suggests that lncRNAs also play a role in regulating cellular functionality and pathogenesis in TC (5).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that lncRNAs possess various regulatory functions in cancer progression, including proliferation, migration, and invasion [ 7 ]. lncRNA taurine upregulated gene 1 (TUG1) is one of the first identified lncRNAs associated with human diseases [ 8 ]. For example, TUG1 promotes cell proliferation and inhibits apoptosis by targeting AURKA in epithelial ovarian cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%